PERFORMANCE OF SOLAR PHOTOVOLTAIC MODULE THROUGH COMBINED AIR AND WATER COOLING IN WARM AND HUMID CLIMATIC CONDITION OF INDIA - Ghosal, M K; Sethi, Ashapurna; Behera, D (MATTER: International Journal of Science and Technology, 2020)
A study was conducted to evaluate the performance of solar photovoltaic module through combined air and water cooling arrangements in warm and humid climatic condition i.e. in Odisha in India during winter and summer months. Solar photovoltaic system requires neither fuel nor produces any pollutant resulting into its increased importance in today’s energy sector. The electrical output from a solar panel is a function of its efficiency and some other controlling parameters which affects the same. One of the major parameters controlling the efficiency of the panel is the temperature as it goes on increasing while using the panel in the sun. About 31 % of the incident solar radiation on the panel is converted into the useful energy and the rest part is stored in its back side causing the rise of temperature and adversely affecting its output. The stored thermal energy is of no use and decreases the durability of the in-built components of the panel due to the impact of severe thermal stresses on them resulting into reduction in its life span and conversion capability. The simplest way to enhance the efficiency of the panel is to incorporate the various cooling arrangements such as air cooling, water cooling and combined air and water cooling and assessing their effectiveness without any cooling arrangement. From the studies, it was observed that the efficiencies of solar panel were enhanced in the range of 8-11 %, 12-15% and 16-20% in air, water and combined air and water cooling respectively compared to without cooling in a clear day.